(untitled) (Research, Society and Development, 2021)
Objective: To report a case of neonatal malformation of three types: supernumerary finger on the left hand, ambiguous genitalia and impervious anus. Method: The present study is a case report, with information obtained through the review of documentary ase of the medical record type. Discourse: It is believed that knowing the profile of children born with congenital malformation is important for assistance, in the sense of offering subsidies to improve the quality of the professional demand provided in the birth of a child with congenital malformation. For the reduction of morbidity and mortality rates in the neonatal period, it is necessary to know the regional particularities of each service, such as the frequency of congenital malformations, the identification of associated risk factors, in addition to valuing early diagnosis, primary and secondary preventions. . Therefore, it is worth mentioning that the existence of some type of congenital malformation both at birth and in the cause of the death of children is linked to underreporting, that is, there are still flaws in collecting information about this type of occurrence observed in all regions. from Brazil, which reveals the importance of working more strongly on promotion and prevention policies, aimed at maternal and child health, so that the occurrence of malformations is minimized. Conclusion: Thus, the contribution of this study is of great relevance for guiding the adoption of measures to strengthen the prenatal policy with preventive measures and the design of strategic actions to combat preventable factors and causes in order to reduce these changes that may bring irreversible consequences to neonates in their growth and development process.